2022
DOI: 10.1155/2022/9142395
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effect of Hemp Seed Oil from the Northern Morocco Endemic Beldiya Ecotype in a Mice Model: Comparison with Fenofibrate Hypolipidemic Drugs

Abstract: Introduction. Cannabis sativa is a source of oil seeds for pharmaceutical, cosmetic, and food uses. Objective. The aim of this study is to evaluate the hypolipidemic effect of hemp seed oil (HSO) obtained from a local ecotype called “Beldiya.” Methods. The extraction of HSO was carried out by cold press method. Then, the fatty acid and tocopherol composition was analyzed, respectively, by GC-FID and HPLC. The hypolipidemic activity of HSO at a dose of 3.5 and 7 mg/kg body weight was evaluated in Triton WR-1339… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…47,48 Our research showed that the Triton WR-1339 injection increased body weight, visceral adipose tissue mass, triglyceridemia, glycemia and liver lipid content; this is in accordance with previous studies. 21,49…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…47,48 Our research showed that the Triton WR-1339 injection increased body weight, visceral adipose tissue mass, triglyceridemia, glycemia and liver lipid content; this is in accordance with previous studies. 21,49…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Our research showed that the Triton WR-1339 injection increased body weight, visceral adipose tissue mass, triglyceridemia, glycemia and liver lipid content; this is in accordance with previous studies. 21,49 However, the administration of peel extract significantly lowered the concentrations of TG in plasma, liver, and adipocytes, while raising their levels in bile and feces. This result suggests that the tested extract could increase the clearance of TG-rich lipoproteins by peripheral organs via increased lipoprotein lipase activity, as hypothesized by Jawed et al 50 Moreover, significant reductions in body weight gain and liver and adipose mass were seen in the treated groups.…”
Section: Papermentioning
confidence: 99%
See 2 more Smart Citations
“…The levels of LDL-C were decreased by 61%, and the levels of HDL-C increased by 324%. These changes resulted in reduced atherogenic index and LDL/HDL ratio [ 186 ]. On the other hand, in a study by Majewski and Jurgoński supplementation of obese male Zucker rats with hemp seed oil (4% diet) decreased the concentration of HDL and triglycerides, but did not affect total cholesterol levels [ 187 ].…”
Section: Chemical Content Of Seeds Eaten Separately and Biological Ac...mentioning
confidence: 99%